Strong Spatial Propagation Strength of Meteorological Droughts Exhibits in the Humid—Arid Transition Regions of Mainland China - Mingqiu Nie; Xin‐Min Zeng; Shengzhi Huang; Ning Wang; Irfan Ullah; Wei Fang; Ganggang Bai; Zengxin Zhang; Jian Zhu (Geophysical Research Letters)
Abstract Spatial propagation strength (PS) is a critical characteristic of drought propagation, reflecting the degree of drought impact in one region relative to another. Here, we quantified PS of meteorological drought for the first time from the perspective of abnormal moisture transmission, and developed a novel framework, combining PS with the original complex network framework, to explore the topological characteristics of drought in mainland China (MC). The results show that non‐positive PS may misrepresent dependency of synchronous droughts, and such instances are widespread in MC (60.4%). Based on dependent droughts, network coefficients derived from the framework indicate that high values of positive PS are predominantly distributed in the humid‐arid transition zones. In these regions, droughts control most of the spatial propagation information, similar to droughts around the edge of the Tibetan Plateau. Our results highlight the importance of PS in drought propagation and could improve drought predictability.